CGROWTH OF TROPICAL TREE SPECIES IN THE COLLECTION FROM QUEVEDO TECHNICAL STATE UNIVERSITY - Suatunce Cunuhay, Pedro (2009)
The growth performance of 40 tropical tree species UTEQ, located in “La Represa” farm near by Quevedo, Ecuador are presented. Four different phases were established with 10 species each one. Each specie were considered as a treatment and a random blocks design with two replications was used. Each plot has a surface of 225 m2 (15 x 15 m). Diameter and height of the trees was measured in each treatment. Significant differences among the species were found for the diameter, height and volume of the trees. It is also presented the flowering and fruiting periods of some species.